Synthesis and Fungicidal Activity of 5‐Aryl‐1‐(aryloxyacetyl)‐3‐(tert‐butyl or phenyl)‐4‐(1H‐1, 2, 4‐triazol‐1‐yl)‐4, 5‐dihydropyrazole. (7th March 2013) - Mao, Hui‐Yu; Song, Hong; Shi, De‐Qing
<x xml:space="preserve">Abstract</x> A series of novel 5‐aryl‐1‐(aryloxyacetyl)‐3‐(tert‐butyl or phenyl)‐4‐(1H‐1, 2, 4‐triazol‐1‐yl)‐4, 5‐dihydropyrazole 1–1 were synthesized by the annulation of 2‐aryloxyacetohydrazides with 3‐aryl‐1‐t‐butyl (or phenyl)‐2‐(1H‐1, 2, 4‐triazol‐1‐yl)prop‐2‐en‐1‐ones (1) in the presence of a catalytic amount of acetic acid. Compounds 1 were obtained by the Knoevenagel reactions of 1‐t‐butyl (or phenyl)‐2‐(1H‐1, 2, 4‐triazol‐1‐yl)ethanone (1) with aromatic aldehydes in the presence of piperidine. Their structures were confirmed by IR, 1H‐NMR, ESI‐MS, and elemental analyses. The preliminary bioassay indicated that some compounds displayed moderate to excellent fungicidal activity. For example, compounds 1, 1, and 1 possessed 100% inhibition against Cercospora arachidicola Hori at the concentration of 50 mg/L.